Transformasi Digital: Program Inovasi Bali Smart Island dalam Peningkatan Kualitas Pelayanan Publik di Bali - Desi Budha Jayanti, Ni Wayan; Sjamsuddin, Sjamsiar; Saleh, Choirul (Jurnal Ilmiah Administrasi Publik, 2024)
Digital transformation impacts various sectors of life, including business, government, and society. The implementation of electronic-based government is the focus, supported by various regulations to produce improved quality of public services through the Bali Smart Island Innovation Program launched by the Bali Provincial Government. This study aims to describe and analyze the Bali Smart Island innovation program in improving the quality of public services in Bali Province and analyze the supporting and inhibiting factors by using a   qualitative method   with  a  descriptive  research The results of the study, the Bali Smart Island innovation program in improving the quality of public services has optimally fulfilled the assurance indicator which is assessed from security and no data leakage. Supporting factors consist of political push, pressure for economy and improved efficiency, and pressure for economy and improved efficiency. While the inhibiting factors show that of the eight factors only two factors occur in the Bali smart Island innovation program in improving the quality of public services, namely; short-term budget and planning, and administrative pressures and obstacles.